Актуальні проблеми окреслення переліку правоохоронних органів України: теоретико-правові засади та значення для правозастосовчої практики (на прикладі органів Державної служби України з надзвичайних ситуацій) - Іванцов, В. О.; Ivantsov, V. O.; ORCID: http://orcid.org/0000-0002-2904-0466 (Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2020. - № 3. - С. 83-89, 2020)
Проаналізовано положення чинних нормативно-правових актів, які стосуються окреслення переліку правоохоронних органів в Україні. Теоретико-правові засади встановлення належності державного органу до переліку правоохоронних органів отримано завдяки оцінці статусу Державної служби України з надзвичайних ситуацій. Зокрема, доведено, що органи ДСНС не належать до правоохоронних органів, а їх посадових осіб не можна визнати працівниками правоохоронного органу. Наголошено, що запропонований автором правовий підхід може бути цілком застосовний до інших суб’єктів владних повноважень, що в перспективі надасть можливість окреслити вичерпне коло правоохоронних органів України.

It is emphasized that the current legislation uses the terms "law enforcement agency", "law enforcement officer", which is directly correlated with law enforcement activities, which in turn indicates the unconditional relevance of the current study. This article analyzes the current legislation in order to separate law enforcement agencies from other government agencies, in order to assign certain positions of government agencies to law enforcement officers. As a result, the imperfections of the definitions of Ukrainian legislation for unambiguous identification of both law enforcement activities and the list of law enforcement agencies have been established. Theoretical and legal bases for establishing the affiliation of a state body to the list of law enforcement agencies in terms of practical implementation of current regulations are obtained by assessing the status of the Civil Service of Ukraine for Emergencies, namely: the assignment of a body to law enforcement should be carried out separately , taking into account the legal position (status) of such body defined in normative legal acts; if the endowment of a certain entity with the status of a law enforcement body has not occurred normatively, it is necessary to proceed from the analysis of the purpose (tasks) and basic functions assigned to a particular body and, accordingly, the powers vested in such a body It has been proved that SES bodies do not belong to law enforcement bodies, as they belong to the unified state system of civil protection (SES bodies are not assigned law enforcement tasks and / or functions; they are not endowed with law enforcement powers), and their officials cannot be recognized as law enforcement officers. body. It is emphasized that the legal approach proposed by the author to establish the affiliation of a state body to the list of "law enforcement agencies" may be fully applicable to other subjects of power, which in the future will provide an opportunity to outline the comprehensive range of law enforcement agencies in Ukraine.

Проанализированы положения действующих нормативно-правовых актов, касающихся определения перечня правоохранительных органов в Украине. Теоретико-правовые основы установления принадлежности государственного органа в перечень правоохранительных органов получено благодаря оценке статуса Государственной службы Украины по чрезвычайным ситуациям. В частности, доказано, что органы ДСНС не относятся к правоохранительным органам, а их должностных лиц нельзя признать работниками правоохранительных органов. Отмечено, что предложенный автором правовой подход может быть вполне применим к другим субъектам властных полномочий, в перспективе позволит определить исчерпывающий круг правоохранительных органов Украины.
Current problems of outlining the list of law enforcement agencies of Ukraine: theoretical and legal principles and significance for law-enforcement practice (on the example of the State Emergency Service of Ukraine)
Іванцов, В. Актуальні проблеми окреслення переліку правоохоронних органів України: теоретико-правові засади та значення для правозастосовчої практики (на прикладі органів Державної служби України з надзвичайних ситуацій) / Володимир Іванцов // Науковий вісник Дніпропетровського державного університету внутрішніх справ. - 2020. - № 3. - С. 83-89. - DOI: 10.31733/2078-3566-2020-3-83-89.
Keywords: Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правоохоронні органи; державний орган; правоохоронні функції; правовий статус; Державна служба України з надзвичайних ситуацій; правоохранительные органы; государственный орган; правоохранительные функции; правовой статус; Государственная служба Украины по чрезвычайным ситуациям; law enforcement agencies; state body; law enforcement functions; legal status; State Service of Ukraine for Emergencies